Legal facts and dynamics of labor relations - Сімутіна, Яна Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
The article investigates the legal facts in their interaction with labor relations. It is claimed that the legal facts are not part of relationships, and the prerequisites of movement in which the past constantly. In addition, legal facts serve as legal basis in dynamics of the legal personality. It is possible to talk about the dynamics of relationships in the broad and narrow sense. In particular, in case of change of legal regulation of social relations is dynamic relations in the broadest sense. This change is usually significant temporal duration associated with the function of the right to respond quickly to changing social relations is natural and cannot be overcame. In the narrow sense should talk about the dynamics of relationships as independent legal phenomenon that occurs through the legal fact in the period from inception to their legal termination and involves changing the basic model of the employment relationship as defined in the employment contract. Thus, the relationship as the most common kind of implementation of legal regulations arise, change and stop not by itself, but because of the specific circumstances which are envisaged by legal norms. Such life circumstances that aht called legal facts, firstly, are determined (recognized as such) in legal norms, and, secondly, they entail legal consequences, including specifying the statutory rights and obligations, that lead to their transformation in subjective. In labor law legal facts have their branch specificity, which appears at some stage of the employment relationship. Thus all stages of the dynamics of labor relations do not exist in isolation from each other and are part of a process in which legal development is by laminating some new facts on factual basis, that already exists. It is substantiated that the impact of legal facts on the dynamics of labor relations involves not only the occurrance, change and termination of relationship as traditionally considered in the theory of law, but also the ability of legal fact cause other legal consequences, for example, suspend or pause labor relations. Special attention was paid to study the concept of suspension of labor relations and prospects of consolidation of this concept in national labor legislation, in particular, in the draft Labour Code of Ukraine.